The 15th Congress of the Asian Society of Transplantation (CAST) was hosted in Cebu, The Philippines, November 27-30, 2017 PREFACE - Danguilan, Romina A (ELSEVIER SCIENCE INC, 2022)
10.1016/S0041-1345(18)31353-8